A situation analysis of child delivery facilities at primary health centers (PHCs) in rural India and its association with likelihood of selecting PHC for child delivery - Akif Mustafa (BMC, 2021)
Abstract Background Primary Health Centers (PHCs) are crucial in providing primary and secondary level healthcare services in rural India. Despite immense efforts and huge funding, a very small proportion of deliveries are carried out at PHCs. The present study aims to explore the availability of facilities at PHCs and its association with likelihood of delivering the child at PHC. Methods We extracted PHC level health infrastructure data from Health Management and Information system (HMIS) and created ‘Facility Index’ using exploratory factor analysis. We merged the ‘Facility Index’ with data of the 4th National Family Health Survey (NFHS-4) to explore the relationship between availability of facilities and healthcare-seeking behavior. Bivariate analysis and multilevel logistic regressions were employed to analyze the association between Facility Index and the likelihood of delivering the child at PHC. Results Availability of facilities (Facility Index) was found to be positively associated with utilization of PHC for childbirth but up to only a certain level of Facility Index. Women living in districts with ‘good’ Facility index were having 2.45 (OR = 2.45; 95% CI: 2.12–2.84) times higher odds of delivering the child at PHC compared to women living in districts with ‘very poor’ Facility Index; however, the odds ratio decreased to 2.11 (95% CI: 1.83–2.43) for ‘Very Good’ Facility Index. The regression line and predicted probabilities also exhibited similar results. Conclusion Based on the findings, we conclude that improvement in availability and quality of facilities might help in improving healthcare utilization from PHCs up to a certain level.